Peran Interpersonal Trust dan Harga Diri Terhadap Pengungkapan Diri Pada Mahasiswa Pengguna Multiple Account Instagram di Bali - Mahayani, Made Tarisa Indira; Bajirani, Made Padma Dewi (Jurnal Ilmiah Wahana Pendidikan, 2025)
One of the Instagram features currently gaining popularity is the multiple account features. This feature allows users to use more than one account, often referred to as having a multiple account. The dynamics of multiple account users tend to revolve around concerns over negative comments made by followers regarding the posts shared by individuals. Additionally, multiple account users feel more confident in posting on their multiple account, as the followers on this account are typically close acquaintances, such as family, friends, and peers. This study aims to examine the role of interpersonal trust and self-esteem in self disclosure among college students wo use multiple Instagram accounts in Bali. The sampling technique used in this research is non-probability sampling, specifically incidental sampling. The Self-Disclosure Scale has an Alpha coefficient of 0,883, the Interpersonal Trust Scale has an Alpha coefficient of 0,929, and the Self-Esteem Scale has an Alpha coefficient of 0,900. The result of this study indicate that both interpersonal trust and self-esteem simultaneously contribute to self-disclosure. Furthermore, there is a positive relationship between interpersonal trust and self-disclosure. Likewise, there is a posivite relationship between self-esteem and self-disclosure